2008
DOI: 10.1021/ic702126k
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonate- and Ester-Substituted 2-Cyanoethylene-1,1-Dithiolate Clusters of Zinc: Aerial CO2 Fixation and Unusual Binding Patterns

Abstract: Treatment of [Zn(tmeda)Cl2] (tmeda = N, N, N', N'-tetramethylethylenediamine) with a phosphonate-substituted 2-cyanoethylene-1,1-dithiolato ligand in air yields a tetranuclear zinc-carbonate complex 1 having the formula of [Zn4(tmeda)3(mu3-CO3){S2CC(CN)P(O)(OEt)2}3] in which four zinc atoms form a trigonal pyramid with the apical zinc atom in a hitherto unknown S3O3 coordination sphere. It is the first example of aerial CO2 fixation to afford a metal-carbonato compound incorporating 1,1-ethenedithiolate ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…The asymmetric n 3 stretching vibrations are observed over the 1454-1320 cm À1 region. This spectrum is common for d 9 Cu 2+ in strongly tetragonally distorted octahedral environment due to strong Jahn-Teller distortion, where the two elongated axially coordinated atoms are Cu1-O5 (perchlorate) and Cu1-O1 0 (carbonate) with bond distances of 2.469 and 2.648 Å, respectively (see X-ray description of complex 1). The in-plane n 4 deformation is found around 770 cm À1 , and the n 2 band due to the out-of-plane deformation is observed at 836 cm À1 .…”
Section: Infrared and Electronic Spectramentioning
confidence: 97%
See 2 more Smart Citations
“…The asymmetric n 3 stretching vibrations are observed over the 1454-1320 cm À1 region. This spectrum is common for d 9 Cu 2+ in strongly tetragonally distorted octahedral environment due to strong Jahn-Teller distortion, where the two elongated axially coordinated atoms are Cu1-O5 (perchlorate) and Cu1-O1 0 (carbonate) with bond distances of 2.469 and 2.648 Å, respectively (see X-ray description of complex 1). The in-plane n 4 deformation is found around 770 cm À1 , and the n 2 band due to the out-of-plane deformation is observed at 836 cm À1 .…”
Section: Infrared and Electronic Spectramentioning
confidence: 97%
“…35,36 The chemical fixation and activation of CO 2 by metal complexes may lead to the development of certain devices that can eliminate the CO 2 present in the air and hence control its concentration and reduce environmental problems due to the greenhouse effect. 6,17,18,25,38 The bonding modes of the carbonato bridging ligand include complexes with dinuclear m 2 -CO 3 , 2-4,6,10,12-18 trinuclear m 3 -CO 3 , 5,[7][8][9]11,16,[18][19][20][21][22][23][24]38,39 and tetranuclear m 4 -CO 3 24-27 coordination modes, as well as 1D, 2D and 3D-dimensional structures. 37 The coordination chemistry of the carbonato ligand in transition metal complexes is very rich due to the versatility of the planar carbonate anion to act as a bridging ligand and hence bind more than one metal ion simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of CO 2 and water (H 2 O) on earth is responsible for the broad range of carbonate minerals which build the earth's lithosphere, and yet, they are found seldom in contemporary chemistry. [22][23][24] Only a few reports have shown that CO 2 from the atmosphere is found in metal-organic coordination architectures or organic scaffolds. [25][26][27] When a H 2 O molecule is H-bonded to CO 3 2− , the resultant supramolecule has numerous accessible oxygen (O) atoms for metal coordination, and thus, could potentially template the assembly of Ag atoms in a specific fashion to form distinct Ag nanoclusters.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the abovementioned aspects, the chemical fixation and activation of CO 2 via transition metal complexes have drawn extensive interest due to the intriguing coordination chemistry of CO 2 (refs 32-34) and its hydration products 28,[35][36][37][38][39] . In the zinc area, triply bridging carbonate units are often found in the solid structures of multinuclear zinc complexes and coordination polymers.…”
mentioning
confidence: 99%